Sectoral effects of exchange rate shocks: Goods exports and the appreciation of the Swiss Franc in 2015 - Andreas Brunhart; Martin Geiger (Liechtenstein-Institut, 2022)
Using granular customs data, we construct a counterfactual of the evolution of Swiss goods exports under the premise that the minimum exchange rate policy would have been continued. We study the dynamic adjustment of aggregate and sectoral goods exports due to the exchange rate shock in January 2015. In absence of a comprehensive J-curve type adjustment we find that Swiss nominal export values increase in Euro, while they drop in Swiss Franc. In real quantities, exports remain largely unaffected indicating a high degree of resilience of the Swiss export industry. On the sectoral level, we observe heterogenous adjustment of exports consistent with varying degrees of flexibility for supply side adjustment and market power.
Keywords: F14; F31; F41; 330; exchange rate shock; goods exports; export sectors; synthetic control method